Proof of Default in Oral Loan Agreements: A Normative Analysis of Civil Law Evidence in Indonesia - Paulus Dominggu Soplanit; M. Syahrul Borman; Dedi Wardana Nasution (International Journal of Law and Society, 2026)
Oral loan agreements remain a prevalent form of contract in Indonesian society, particularly within familial relationships, friendships, and informal financial transactions. This study aims to examine the legal standing of oral loan agreements under the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata/KUHPerdata) and to analyse the evidentiary mechanisms applicable in cases of default (wanprestasi). This research employs a normative juridical approach, utilising secondary data sources comprising legislation, legal doctrines, and relevant court decisions. The findings indicate that oral loan agreements are legally valid and binding provided they satisfy the requirements stipulated in Article 1320 of the Civil Code, namely mutual consent, legal capacity, a specific object, and a lawful cause. However, the fundamental weakness of such agreements lies in the evidentiary challenges that arise during dispute resolution. In the absence of written documentation, proof of the agreement's existence and content must rely on alternative forms of evidence, including witness testimony, acknowledgement by the parties, bank transfer records, receipts, electronic communications, and circumstantial evidence as recognised under Article 1866 of the Civil Code and the Electronic Information and Transactions Law. The success of claims in default cases largely depends on the strength, consistency, and relevance of the evidence presented. This study concludes that while oral agreements possess full legal force, parties are strongly advised to document loan transactions in writing or secure supporting evidence to ensure greater legal certainty and facilitate effective dispute resolution.